Usulan Perancangan Tata Letak Fasilitas Bengkel Las Dengan Metode Systematic Layout Planning - Galuh Meistuti Kusuma Prasasti; Febrina Agusti; Garnet Filemon Waluyono (Politeknik Kampar, 2025)
Welding workshop is a business engaged in iron and mild steel welding services. The welding workshop, which has been established since 2000 until now, often produces flower pot racks of various shapes and sizes. In the initial observation, production activities were carried out less than optimally due to the inefficiency of moving material, the distance of movement, causing delays in product processing. In this study the method used by researchers is the systematic layout planning method with the aim of producing a more efficient flow through layout design by paying attention to the sequence of a process relationship to each activity that occurs. Based on the Systematic Layout Planning method, there are proposed layouts with distances between departments that are shorter or closer to the distance between departments, with a comparison of the distance between the initial layout of 16 m and the proposed layout of 11.37 m.